Individuation in the novels of Toni Morrison : a Jungian perspective - Braema Mathiaparanam. (2009)
Toni Morrison deals with fragmented African-American individuals. In her fiction, she examines the causes and reveals the pain in being institutionally marginalised because of one's colour, class and/or sex. She looks to re-claim for some of her characters a sense of identity by dismantling the predominant order. This is an act of recovery and establishing a new paradigm for the African-American in the America of the late twentieth century. Recovery begins at an individual level and Morrison asserts that African-Americans need to address the past and relate to this history and their African-American heritage. This is a journey of self-discovery.